If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 = 6(x + 8) Reorder the terms: 3 + 6x = 6(x + 8) Reorder the terms: 3 + 6x = 6(8 + x) 3 + 6x = (8 * 6 + x * 6) 3 + 6x = (48 + 6x) Add '-6x' to each side of the equation. 3 + 6x + -6x = 48 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + 0 = 48 + 6x + -6x 3 = 48 + 6x + -6x Combine like terms: 6x + -6x = 0 3 = 48 + 0 3 = 48 Solving 3 = 48 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -6(0)-6y=36 | | 2y^2-3y+9=0 | | 2x+7=2x-2.5 | | -6x-6(0)=36 | | 10-(3z-5)=1-4z | | N+2(3-1)=8 | | w+w-w+4w+w=18 | | 15m-4m-2m-8m=17 | | 0.625=N+0.25 | | -5y=-15x-12 | | X=2[13+(8-5)] | | 8+0.2(x-300)=36.60 | | 2(4x-3)-6= | | w-w+2w+2w-3w-1=14 | | 2x+30=-3x | | ln(x)=.67 | | .5x+1=1.5x-8 | | 1500=x(1+.05)18 | | 8p-6p=20 | | 2n+1=2*1 | | -.5x-5=-11 | | 8(-48x-36)=-10(12-8x) | | 6j-4j=14 | | 5x+3=9x+15-x | | -7u-6u+-4u=17 | | 2014-5x=-41 | | 6x-8(0)=-48 | | 6x-13=-5x-2 | | 16w-3w-10w-3w+-4w=20 | | 16w-3w-10w-3w+-4w=10 | | 3N=123 | | 6v-3v+5v-7=9 |